2021
DOI: 10.1186/s12889-021-11001-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of average temperature on suicide rates in five urban California counties, 1999–⁠2019: an ecological time series analysis

Abstract: Background Suicide is among the top 10 leading causes of premature morality in the United States and its rates continue to increase. Thus, its prevention has become a salient public health responsibility. Risk factors of suicide transcend the individual and societal level as risk can increase based on climatic variables. The purpose of the present study is to evaluate the association between average temperature and suicide rates in the five most populous counties in California using mortality d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…Our results suggest that higher temperature was associated with an increased risk of suicide death with an approximately linear relationship, which is consistent with previous studies . For example, a multicountry analysis indicated that higher ambient temperature was associated with increased risks of suicide death, with the country-specific RRs ranging from 1.31 in the US to 1.61 in South Korea, which is comparable to our estimate (RR = 1.44).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that higher temperature was associated with an increased risk of suicide death with an approximately linear relationship, which is consistent with previous studies . For example, a multicountry analysis indicated that higher ambient temperature was associated with increased risks of suicide death, with the country-specific RRs ranging from 1.31 in the US to 1.61 in South Korea, which is comparable to our estimate (RR = 1.44).…”
Section: Discussionsupporting
confidence: 92%
“…mately linear relationship, which is consistent with previous studies. 13,17,18,22 For example, a multicountry analysis indi-cated that higher ambient temperature was associated with increased risks of suicide death, with the country-specific RRs The associations were presented as the cumulative relative risks comparing a given temperature with the minimum-mortality temperature over a 0-to 3-day lag. The solid lines are mean risk estimates, and the shaded areas are their 95% CIs.…”
Section: Discussionmentioning
confidence: 99%
“…Extreme weather events elevate the risk of symptom exacerbation (cf. Lõhmus [ 58 ]), suicide [ 8 , 13 , 14 , 15 ], and a three-times-higher risk of mortality during heatwaves compared to people without mental disorders [ 18 ]. Other marginalized groups constitute women (especially pregnant or postnatal women), children, groups with less social support, insufficient medical care, people suffering from financial difficulties, and minoritized ethnic groups [ 3 , 23 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data particularly show negative consequences related to ambient temperature and heat, with an increase in temperature being associated with an increase in mental distress, hospitalizations for mental disorders (including bipolar disorder, schizophrenia, and dementia) [ 8 , 10 , 11 , 12 ], and increased suicide rates [ 6 , 8 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extreme weather events elevate the risk of symptom exacerbation (cf. Lõhmus [57]), suicide [8,[13][14][15], and a three times higher risk of mortality during heatwaves compared to people without mental disorders [18]. Other marginalized groups constitute women (especially pregnant or postnatal women), children, groups with less social support, insufficient medical care, people suffering from financial difficulties, and minoritized ethnic groups [3,23,[64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%